"L'Invitation au voyage" de Baudelaire : une analyse évocative - Rodriguez, Hugo (Cognitive philology, 2014)
This article proposes an analysis of Baudelaire's "L'Invitation au voyage" under the scope of Marc Dominicy's theory of poetic evocation. This theory, recent in its final form, brings together the philological, metrical and cognitive dimensions of a poem. It aims to describe the cognitive mechanisms intentionnally released by the poem, through its double organisation (linguistic and metrical), and their specific effects, which consists in focusing the reader's attention on the representational truth or falseness rather than the usual semantic truth or falseness. In the case of "L'Invitation au voyage", the evocative mechanisms are based on a syncretic use of many different references : romance, Goethe's Mignon, Gautier's Albertus, Holland, orientalism, Lost Paradise, Weber's music, etc. They enable to show how Baudelaire has conceived his poem not, as it is often claimed, as a real travel of a couple to a paradisiac country, escaping from the Spleen of the real world, but as a love quest and request to an imaginary paradisiac country (l'Idéal) shaped by the poet and accessible through the Spleen and not without it.